Corruption Perceptions and Their Impact on Macroeconomic Performance in Iraq: Institutional Transmission Channels and ARDL Evidence from the Model (2010–2022) (المجلة الدولية للبحوث العلمية, 2026)
The paper structurally analyzes the impact of perceived corruption on Iraq’s macroeconomic performance during the period 2010–2022. More specifically, it attempts to determine the elasticity of major macroeconomic variables exchange rate, inflation, and gross domestic product with respect to changes in Transparency International’s Corruption Perception Index (CPI). Annual time series data is used within an autoregressive distributed lag (ARDL) framework after checking stationarity through Augmented Dickey Fuller (ADF) test and bounds testing approach toward cointegration. Long-run equilibrium association between corruption and economic performance is found to be highly significant by this study. Administrative perception explains a substantial proportion of variation of GDP as well as 65% variation in exchange rate explained by perceptions on administration. There exists strong negative association where higher-level administrative type -corruption directly associates with declining GDP besides depreciation over local currency’s purchasing power. It found outcomes attributable to the dependency of the Iraqi economy on oil revenues and weak institutions in the country. Therefore, this study has assumed that transparency shall be improved and corruption reduced within public offices by implementing urgent policy interventions as a prerequisite for economic stability together with diversification of an economic base away from a rentier state model.